Esophageal food impaction during cultural holidays and national athletic events. (22nd December 2016) - Shuja, Asim; Winston, Diana M.; Rahman, Asad Ur; Mitty, Roger D.; Jaber, Bertrand L.; Keo, Thormika
Abstract : Background: Although intrinsic risk factors contributing to esophageal food impaction are well established, whether social behavior affects its occurrence has not yet been examined. Methods: We conducted a retrospective review of the gastroenterology endoscopy procedural documentation software for the period of 2001–2012 to identify all patients who presented to our emergency department for esophageal foreign-body removal at the time of national athletic events and holidays associated with dietary indiscretions. Results: We found that adults undergoing emergent esophagogastroduodenoscopy during periods celebrating cultural holidays and national athletic events were more likely to experience esophageal food impaction compared with those undergoing emergent endoscopy during periods not associated with these events (36.8% vs 3.6%; P < 0.001): a 10-fold increase. During a national holiday/athletic event period, the most common impacted food item was turkey (50%) followed by chicken (29%) and beef (21%). Conclusions : Esophageal food impaction is more likely to occur on American holidays and national athletic events and is associated with large meals. Patients with intrinsic risk factors should be advised to modify their diet during cultural events associated with tachyphagia and large meals to prevent esophageal food impaction.